Estimating the Impact of Cash Transfer on Spending Behaviour: Utilizing IFLS - Bintang Satrio Wibowo,; Ahmad Syahrul Fauzi,; Deky Aji Suseno,; Shanty Oktavilia, (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
Government cash transfer programs aim to assist individuals or households in escaping poverty. However, concerns have arisen regarding the misuse of such assistance for tertiary expenditures, such as tobacco and alcohol. This study aims to evaluate the impact of government assistance on household consumption patterns in Indonesia. Utilizing data from the Indonesia Family Life Survey (IFLS), we apply Ordinary Least Squares (OLS) and Instrumental Variable Regression approaches to analyze this impact. The results indicate that an increase in cash transfer amounts contributes to an overall increase in household expenditures, including tertiary consumption. A significant positive relationship between cash transfers and tertiary consumption expenditures suggests the potential for moral hazard issues among certain households in Indonesia